Citizen Science in Ireland - Roche, Joseph; Ni Shuilleabhain, Aoibhinn; Mooney, Peter; Barber, Gillian L.; Bell, Laura; Ryan, Cliodhna (Frontiers in Communication, 2021)
Ireland has a rich history of public engagement with science and the growing number of national citizen science initiatives is in keeping with developments seen in other European countries. This paper explores several aspects of citizen science in Ireland, in order to assess its development and to better understand potential opportunities for the field. An introduction to the roots of citizen science in Ireland’s past, from the first methodical observations of natural phenomenon carried out at monastic settlements up to present day projects monitoring environmental change and biodiversity, is presented along with an overview of the current national citizen science projects running in the country. This cataloguing of contemporary citizen science will be compared to the awareness of citizen science in the Irish education system at primary, post-primary, and university level. These measures of progress will be considered in the changing context of international citizen science funding and available support, such as the European Citizen Science Association and the EU-Citizen.Science platform. Citizen science in Ireland is at a critical point. If citizen science is embraced as a truly social and participatory innovation, Ireland has the chance to not only dramatically improve its citizen science output, but to also become a model of best practice for countries at similar stages of citizen science development.